Betula pendula trees infected by birch idaeovirus and cherry leaf roll virus: Impacts of urbanisation and NO2 levels. (15th June 2023) - Gilles, Stefanie; Meinzer, Meike; Landgraf, Maria; Kolek, Franziska; von Bargen, Susanne; Pack, Kaja; Charalampopoulos, Athanasios; Ranpal, Surendra; Luschkova, Daria; Traidl-Hoffmann, Claudia; Jochner-Oette, Susanne; Damialis, Athanasios; et al.
Abstract: Viruses are frequently a microbial biocontaminant of healthy plants. The occurrence of the infection can be also due to environmental stress, like urbanisation, air pollution and increased air temperature, especially under the ongoing climate change. The aim of the present study was to investigate the hypothesis that worsened air quality and fewer green areas may favour the higher frequency of common viral infections, particularly in a common tree in temperate and continental climates, Betula pendula ROTH. We examined 18 trees, during the years 2015–2017, the same always for each year, in the region of Augsburg, Germany. By specific PCR, the frequency of two viruses, Cherry leaf roll virus (CLRV, genus Nepovirus, family Secoviridae), which is frequent in birch trees, and a novel virus tentatively named birch idaeovirus (BIV), which has been only recently described, were determined in pollen samples. The occurrence of the viruses was examined against the variables of urban index, air pollution (O3 and NO2 ), air temperature, and tree morphometrics (trunk perimeter, tree height, crown height and diameter). Generalized Non-linear models (binomial logit with backward stepwise removal of independent variables) were employed. During the study period, both CLRV and BIV were distributed widely throughout the investigated birch individuals. CLRV seemed to be rather cosmopolitan and was present independent of any abiotic factor. BIV's occurrence was mostly determined by higher values of the urban index and of NO2 . Urban birch trees, located next to high-traffic roads with higher NO2 levels, are more likely to be infected by BIV. Increased environmental stress may lead to more plant viral infections. Here we suggest that this is particularly true for urban spaces, near high-traffic roads, where plants may be more stressed, and we recommend taking mitigation measures for controlling negative human interventions. Graphical abstract: Image 1 Highlights: Cherry leaf roll virus and birch idaeovirus presence was studied in Betula pendula pollen. High year-to-year variability was found in viral infections of birch trees. Pollen of urban trees were more highly infected with CLRV and BIV. The higher the urbanity index and the NO2 levels, the more frequent the birch idaeovirus infection.